2019
DOI: 10.7554/elife.48089
|View full text |Cite
|
Sign up to set email alerts
|

A scalable platform for the development of cell-type-specific viral drivers

Abstract: Enhancers are the primary DNA regulatory elements that confer cell type specificity of gene expression. Recent studies characterizing individual enhancers have revealed their potential to direct heterologous gene expression in a highly cell-type-specific manner. However, it has not yet been possible to systematically identify and test the function of enhancers for each of the many cell types in an organism. We have developed PESCA, a scalable and generalizable method that leverages ATAC- and single-cell RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 44 publications
0
79
0
Order By: Relevance
“…Other groups have taken a similar approach using mainly chromatin accessibility data from ATAC-seq experiments to identify REs for use in AAV targeting CINs ( Hrvatin et al, 2019 ; Mich et al, 2020 ; Vormstein-Schneider et al, 2020 ). Candidate regions with enrichment of H3K27ac are likely to give a better success rate than accessible regions determined by ATAC-seq alone because H3K27ac is a more specific mark of active enhancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other groups have taken a similar approach using mainly chromatin accessibility data from ATAC-seq experiments to identify REs for use in AAV targeting CINs ( Hrvatin et al, 2019 ; Mich et al, 2020 ; Vormstein-Schneider et al, 2020 ). Candidate regions with enrichment of H3K27ac are likely to give a better success rate than accessible regions determined by ATAC-seq alone because H3K27ac is a more specific mark of active enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main drawbacks of using a genome-wide screen to identify pREs is that it may identify many false positives, as individual epigenetic markers are not sufficient to prove that a locus will function in the cell type under investigation ( Nord et al, 2015 ; Hrvatin et al, 2019 ; Mehta et al, 2019 ; Mich et al, 2020 ; Vormstein-Schneider et al, 2020 ). However, we postulated that by integrating multiple sources of data we could increase our confidence in the candidate pREs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that this methodological approach of quadruple modality functional characterization can be extended to slice culture with viral labeling as well. This approach is well poised to take advantage of an increasing number of enhancer-driven subclass and type-specific viral tools (Dimidschstein et al, 2016; Hrvatin et al, 2019; Jüttner et al, 2019; Mehta et al, 2019; Nair et al, 2019; Mich et al, 2020; Graybuck et al, 2020; Vormstein-Schneider et al, 2020) to allow prospective targeting of cell classes or subclasses, and subsequent refinement of cell type identity by a combination of marker genes using mFISH. Brain slice culturing and viral transgenesis will allow not only measurement, but also functional manipulation of the human microcircuit, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For CNS applications, this might require the use of viruses engineered to have cell type-specific tropism to allow them to target the meninges or Schwann cells. 18 When these issues have been resolved for syndromic diseases, such techniques could then be used to correct similar mutations in sporadic diseases as well.…”
Section: Genetic Engineering and Antitumor Antibodiesmentioning
confidence: 99%